The Role of the Intelkam Unit in Collecting Former Terrorism Convicts to Prevent the Spread of Radicalism in the Malang Police - Sukmana, Arsyan Kelvin (Advances in Police Science Research Journal, 2024)
Radicalism is a strong desire to change social, cultural, political and economic institutions by using violence to achieve goals. In 2023, there will be 9 former terrorism convicts residing in the jurisdiction of the Malang Police who indicate that they have not adhered to the Pancasila ideology and are adamant about the teachings they adhere to. This could threaten the stability of security and social security and be dangerous for the unity and unity of the Indonesian nation. This writing aims to explain the fundraising efforts carried out by Satintelkam in mobilizing former terrorism convicts in the Malang Police jurisdiction. This research uses the concepts of Satintelkam, mobilization, radicalism, terrorism, as well as role theory and management theory. The research method used is descriptive field research with a qualitative approach through interviews, observation and document study. The results of the research show that (1) the fundraising activities carried out by Unit IV Satintelkam Malang Police have exceeded the specified limits. (2) Implementing coordination with Densus 88 AT often encounters obstacles related to information and data disclosure. (3) Timeliness in carrying out tasks is very poor because there is still a shortage of members (4) the budget is still lacking, (5) the budget absorption process is too complicated and takes a long time, (6) facilities and infrastructure are limited, independence is still very lacking and commitment not working well.